Application of cognitive technologies for the formation of speech dialogue management models - A. A. Solodov; Т. G. Trembach (Открытое образование (Москва), 2019)
Purpose of research.  The aim of the study is the use of cognitive technologies for the formation of speech dialogue management models. At present, for the development of the Internet of things, the expansion of communicative opportunities for their interaction, it is important to improve speech dialogue management models in many areas. The need for dialogue can arise between cyber-physical systems, between a person and cyber-physical systems, between users, developers, and administrators. The speech dialogue management models covers many issues related to processing a speech signal, semantic analysis, understanding the meaning of speech, using cognitive mechanisms for interaction, and some others. A special place among them is occupied by the problem of building a speech dialogue between users, developers, and cyberphysical systems. This article is devoted to the consideration of the use of speech dialogue management models of intelligent systems, as well as users, developers, administrators.Materials and methods of research.  New approaches and methods are required to solve the problems within the framework of the Industry 4.0. The industry 4.0 concept represents a variety of technologies, including the creation of cyber-physical systems, a variety of different protocols for their interaction. One of its main directions is the Internet of things. Cognitive mechanisms associated with the formation and application of concrete sensory images, concepts-representations, concepts-frames are used to solve the problems of model formation. To form the abilities and speech skills for the communicative activities of the participants of the interaction within the framework of the Industry 4.0 concept, the methods associated with mastering foreign language technologies were used. The ultimate goal of their use is to achieve the ability to master spontaneous speech in both everyday and professional situations. Mastering a foreign language involves the use of cognitive technologies, which allows you to develop the structure of mental operations.Results.  Some features of the formation of a voice dialogue management model for intelligent systems and the preparation of interaction participants in the framework of the concept — users, developers, and industrial system administrators  –  are considered. The application of cognitive mechanisms for organizing and using the model of speech dialogue management is shown. The use of conceptual representations and scripting concepts in intelligent systems allows us to develop the structure of the world model. The application of cognitive mechanisms for training interaction participants, within the framework of the Industry 4.0 concept, improves their training by improving understanding of the material being studied by building logical connections and a mental model of the material. Using concepts allows you to build mental models of your own thoughts. At the end of all mental operations, participants in the interaction acquire the ability to form speech dialogue management models.Conclusion.  The use of cognitive technologies makes it possible, both for intelligent systems and for interaction participants, to use generalized static structures of concepts, situations, and dynamic structures for real and mental operations. The active use of such structures makes it possible to better understand the current situation and successfully formulate and use voice dialogue management models for solving problems arising during the development of the Industry 4.0 concept.